HASIL BELAJAR PASSING BAWAH BOLA VOLI MINI MELALUI PENDEKATAN BERMAIN SDN25 BATU AMPAR - Rabiah Rabiah; Victor Simanjuntak; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe research problem is how to improve the passing of volley ball by using auxiliary media in class V SDN 25 BatuAmparKubu Raya. The purpose of this research is to know the effort of increasing passing under volley ball by using media aids in class V SDN 25 BatuAmpar.This study uses classroom action research which is the basis for improving the learning that will be produced, with the following steps: 1) Planning; 2) implementation; 3) observation; 4) reflection; Subjects in use as many as 23 students. Data were collected by questionnaire / questionnaire and test each cycle.From the results of the research In the preliminary test before the action was given that the average value of grade 66.38 and the number of percentage of classical completeness only reached 34.78%. In Cycle 1, shows the average learning outcome of 74.49 with classical mastery 65.22%. While the results of analysis of data cycle 2 obtained average learning outcomes 76.81 with classical completeness of 82.61% and the value of student activity observation the better.Keywords: Passing Bring, Mini Volley Ball, Media Help